Penerapan Media Pembelajaran Video Based Learning Untuk Meningkatkan Minat Belajar Di SDN 017 Seberang Cengar - Afrila, Viona; Salman, Salman; Fithri, Radhiyatul (Cendekia : Jurnal Pendidikan dan Keagamaan, 2024)
The learning process is less interesting and enjoyable due to the lack of variation in the choice of media in learning which causes low student interest in learning in class V of SD N 017 Seberang Cengar. This is characterized by students' lack of enthusiasm for learning, feeling bored, going in and out of class, not paying attention to the teacher. This research aims to students' interest in learning in science subjects by implementing video based learning media in class V of SD N 017 Seberang Cengar. This research method uses a qualitative method with the type of Classroom Action Research (PTK), which consists of two cycles, each cycle consisting of two meetings. The data collection techniques are through observation, interviews and documentation. The research res ults obtained were that student activity in cycle I increased from 50% to 59.3% in the quite good category. In cycle II, student activity increased from 78.1% to 93.7% in the very good category. And student interest in learning in cycle I from 2.00% to 2.25% in the good category. Meanwhile in cycle II it was 3.03% to 3.65% in the very good category. Thus, through the application of video based learning media, it can increase the interest in learning of class V students at SD N 017 Seberang Cengar.